2005
DOI: 10.4012/dmj.24.403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Base Monomer's Refractive Index on Curing Depth and Polymerization Conversion of Photo-cured Resin Composites

Abstract: In this study, we examined the effect of the transmitted amount of visible light through a resin composite on the curing depth and polymerization conversion. Transmitted amount of visible light was strongly dependent on the magnitude of refractive index difference that existed between the resin and silica filler. More specifically, the differences arose from the type of base monomer used. The transmitted amount of visible light exhibited a good correlation with the curing depth and Knoop hardness ratio of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 9 publications
3
65
0
4
Order By: Relevance
“…These properties of the microstructure also affect the overall refractive index of the composite material. It should be noted that in general, magnitude and direction of scattering depends on the average magnitude of refractive index fluctuation in the composite material 12) . Therefore, individual refractive indices of the dispersed phase (fillers) and matrix phase (resin) should be perfectly matched in order to obtain transluceny close to that of tooth tissue 12,13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties of the microstructure also affect the overall refractive index of the composite material. It should be noted that in general, magnitude and direction of scattering depends on the average magnitude of refractive index fluctuation in the composite material 12) . Therefore, individual refractive indices of the dispersed phase (fillers) and matrix phase (resin) should be perfectly matched in order to obtain transluceny close to that of tooth tissue 12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in general, magnitude and direction of scattering depends on the average magnitude of refractive index fluctuation in the composite material 12) . Therefore, individual refractive indices of the dispersed phase (fillers) and matrix phase (resin) should be perfectly matched in order to obtain transluceny close to that of tooth tissue 12,13) . If this were not so, the tooth would have poor esthetical properties and reduced cure depth with visible light 14) .…”
Section: Introductionmentioning
confidence: 99%
“…From the results, the filler loading of centrifuged composites was demonstrated to be affected by monomer type and total filler content. Regarding monomer type, characteristics of the base monomer have an effect on post-curing properties including TANOUE et al 503 polymerization conversion 16) . Conventional composites commonly include such main monomers as 2,2-bis [4-(2-hydroxy-3-methacryloyloxy-propoxy) phenyl] propane (Bis-GMA), UDMA, Bis-MPEPP, and their variations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ytterbium trifluoride would increase the translucency of the composites relative to the use of barium glass alone. 34 Arikawa and others 35 reported that materials with small, irregularly-shaped fillers showed greater %T than those with large, spherically-shaped fillers. Dos Santos and others 25 reported that a composite containing 20 nm filler showed greater %T than that containing 0.6 lm filler.…”
Section: E86mentioning
confidence: 99%
“…Previous reports indicated that the material translucency was high when the refractive indexes of the resin matrix and filler were similar. 34 In TC, barium glass and ytterbium trifluoride provide the radiopacity, with refractive indexes of 1.98 and 1.53, respectively. As the refractive indexes of the resin monomer are between 1.49 and 1.56, the resin monomer is more similar to ytterbium trifluoride than barium glass in terms of refractive index.…”
Section: E86mentioning
confidence: 99%